(untitled) (Revista Electrónica Diálogos Educativos. REDE, 2025)
To Evaluate the Medical Health Services Program, spinal area, aimed at vulnerable students of primary education, high school and special education who, between 2010 and 2016, were beneficiaries of the National Board of School Aid and Scholarships (NBSAS), it is undertaken from an empirical quantitative study, of associative strategy, with a retrospective non-experimental design (ex post facto). Empirical quantitative study, with an associative strategy, and a non-experimental retrospective methodological design (Ex post facto). The sample corresponds to the universe of student’s beneficiaries of NBSAS services between 2010 and 2016 (N=359.074), who are located across the 15 geopolitical regions of Chile, distributed in 344 communes. The results raise a first national report on the public policy implemented. Likewise, the screening showed that alterations on the spine affected 28.8% of the universe, with differences between sexes and types of diagnosis. Our findings show a prominence of composed diagnosis of the type: scoliosis/hyperlordosis for women, and a curved back/dysmetria for men.